Brain Oxygenation in Post-concussion Combat Sport Athletes - Tiberini, Paolo; D'Antona, Giuseppe; Cicchella, Antonio (Frontiers in Sports and Active Living, 2021)
Purpose: Investigate the feasibility of a non-invasive method to evaluate the physical and cognitive repercussions of long-lasting post-concussion effects in professional combat sports athletes. To help athletes return to professional combat, there is a need for unbiased objective tools and techniques used as a prognostic method of recovery after Sport-Related Concussion (SRC). Methods: 6 mild Traumatic Brain Injury (mTBI) and 7 not concussed (NC) participants were tested Inspired/expired gas concentration, Cerebral changes in oxygenated hemoglobin (ΔO2Hb), deoxygenated hemoglobin (ΔHHb), and total hemoglobin were measured using a 3-step protocol (Rest before max VO2 test, Hypercapnia, and recovery after max VO2 test). The Cerebral Vascular Reactivity (CVR) and respiratory parameters of both sample sets were calculated using a non-linear approach. Aerobic fitness outcome was quantified through mean average using the Bruce test. Participants performed Fitt’s test and Analysis of Medial-Lateral and Anterior-Posterior range of oscillation was carried out via a Force Platform Romberg Test. Results: The mTBI participants showed a different association between brain oxygenation, balance, maximal aerobic capacity, and power, in comparison with NC participants. VO2max revealed no significant differences between the two sample sets: 49.58±5.19 for TBI and 47.47±4.91 ml/kg/min-1 for NC. However, the testing of mediolateral sway with eyes open, FetO2 average in hypercapnia, Saturated HbO2 during rest and recovery phase after maximal incremental exercise, revealed significant differences with the mTBI group. Conclusions: it emerges that NIRS is able to reveal differences in long-time outcomes of mTBI, together with lateral sway, in athletes not specifically trained for balance.